Characterization of the complete chloroplast genome of Sparganium glomeratum (Typhaceae) from Jilin Province, China and phylogenetic analysis - Qi-Xiang Lu; Lu-Jie Ren; Ya-Nan Wang; Yao Xiao; Yu-Dong Li; Jia-Nan Ying; Ying Zhang; Ruihong Wang; Zhe-Chen Qi; Zheng-Ying You (Mitochondrial DNA. Part B. Resources, 2021)
The complete chloroplast genome of Sparganium glomeratum was sequenced and assembled in this study. The circular genome is 160,391 bp in length and exhibits a typical quadripartite structure with a large single-copy (LSC, 87,660 bp) and small single-copy (SSC, 18,721 bp) regions, separated by a pair of inverted repeats (IRs, 27,005 bp). The cp genome contains 113 unique genes, including 79 protein-coding, 30 tRNA, and four rRNA genes. The phylogenetic analysis within the Poales showed that Sparganium is monophyletic and most closely related to Typha. Within Sparganium, S. glomeratum is sister to the clade of S. stoloniferum and S. euricarpum. The work reported here will provide useful information for the evolutionary studies on the genus of Sparganium.